Oligarchic Hegemony in Elections: A Criminal Offense Undermining Integrity and Threatening Democracy in Indonesia - Hosnah, Asmak Ul; Antoni, Herli; Rohaedi, Edi; Nuraeny, Henny; Faturachman, Fauzan Azima (Universitas Lampung, 2024)
The election of the President and Vice President serves as a fundamental pillar of democracy and a crucial moment in the democratic process in Indonesia. However, in recent decades, the hegemony of oligarchs has posed a significant threat to the fairness and integrity of the electoral system. Oligarchs, wielding substantial power and influence, frequently manipulate the electoral process for personal and group interests, often resorting to criminal activities such as bribery, political intimidation, and the misuse of state resources. These actions undermine the legitimacy of elections and erode public trust in the democratic process. This research seeks to analyze the methods employed by oligarchs in the presidential election as criminal acts that damage the integrity of the electoral process in Indonesia. Using a normative legal approach, this research examines various written sources, including books, journals, and empirical data from past elections. The findings reveal a consistent pattern of legal violations by oligarchs that significantly compromise the electoral process. Based on these findings, the research recommends reforms aimed at strengthening the enforcement of criminal laws related to elections and enhancing the capacity of electoral oversight institutions to prevent oligarchic interference. These reforms are crucial for preserving an inclusive and fair democracy in Indonesia.